Intrinsic, environmental, and anthropogenic factors related to pronghorn summer mortality. Issue 3 (2nd February 2018) - Reinking, Adele K.; Smith, Kurt T.; Monteith, Kevin L.; Mong, Tony W.; Read, Mary J.; Beck, Jeffrey L.
ABSTRACT: Pronghorn ( Antilocapra americana ) are an iconic wildlife species of sagebrush ( Artemisia spp .) and grassland ecosystems in western North America. Over 50% of pronghorn have historically occurred in Wyoming; however, these populations have declined by nearly 30% in <2 decades, concurrent with expanding energy development and prolonged drought. Research suggests adult female pronghorn, unlike other temperate ungulates, are more likely to die in summer, when body condition is lower from extreme energetic demands of reproduction, which are higher for pronghorn than other ungulates. To evaluate the potential effects of intrinsic, environmental, and anthropogenic factors on summer mortality risk, we monitored 114 adult female pronghorn equipped with global positioning system transmitters in the Red Desert region of south‐central Wyoming, USA between 2013 and 2015. We modeled mortality risk using Cox's proportional hazards regression. Summer mortality risk was influenced by intrinsic and environmental factors; mortality risk increased when individuals were in poorer body condition entering the previous winter and when they experienced greater variation in average daily snow depth during the previous winter. We did not detect an effect of the distance to and density of roads, oil and gas wells, or fences on pronghorn summer mortality. During years of increased winter severity with deep and fluctuating snow depths, managers may observe higher winter mortality and higher mortality the following summer, likely as a consequence of the energetic expense associated with winter survival and spring reproduction for female pronghorn. © 2018 The Wildlife Society. Abstract : We modeled summer mortality risk for pronghorn in the Red Desert region of south‐central Wyoming, USA between 2013 and 2015, and found that poorer body condition entering the previous winter and exposure to greater variation in snow depth during the previous winter increased the risk of death the following summer. In severe winters with more variable snow depths, managers in Wyoming will likely observe higher mortality during the following summer in pronghorn populations.